Observation of extremely strong shock waves in solids launched by petawatt laser heating - Lancaster, KL; Robinson, APL; Pasley, J; Hakel, P; Ma, T; Highbarger, K; Beg, FN; Chen, SN; Daskalova, RL; Freeman, RR; Green, JS; Habara, H; et al. (American Institute of Physics, 2017)
Understanding hydrodynamic phenomena driven by fast electron heating is important for a range of applications including fast electron collimation schemes for fast ignition and the production and study of hot, dense matter. In this work, detailed numerical simulations modelling the heating, hydrodynamic evolution, and extreme ultra-violet (XUV) emission in combination with experimental XUV images indicate shock waves of exceptional strength (200 Mbar) launched due to rapid heating of materials via a petawatt laser. We discuss in detail the production of synthetic XUV images and how they assist us in interpreting experimental XUV images captured at 256 eV using a multi-layer spherical mirror.